Detection of Leishmania spp. in Chronic Dermatitis: Retrospective Study in Exposed Horse Populations - Alessia Libera Gazzonis; Giulia Morganti; Ilaria Porcellato; Paola Roccabianca; Giancarlo Avallone; Stefano Gavaudan; Cristina Canonico; Giulia Rigamonti; Chiara Brachelente; Fabrizia Veronesi (Pathogens, 2022)
Leishmania infantum is a protozoan causing human zoonotic visceral leishmaniasis (ZVL) and visceral–cutaneous canine leishmaniosis (CanL) in the Mediterranean Basin. L. infantum is able to infect a large number of wild and domestic species, including cats, dogs, and horses. Since the 1990s, clinical cases of equine leishmaniasis (EL), typically characterized by cutaneous forms, have been increasingly diagnosed worldwide. The aim of the present study was to evaluate the presence of clinical forms of EL in CanL-endemic areas in Italy, where exposure of equine populations was ascertained from recent serological surveys. For this purpose, formalin-fixed and paraffin-embedded skin biopsies of 47 horses presenting chronic dermatitis compatible with EL were retrospectively selected for the study and subjected to conventional and q-PCR. A singular positivity for L. infantum was found; BLAST analysis of sequence amplicons revealed a 99–100% homology with L. infantum sequences. The histological examination revealed a nodular lymphoplasmacytic and histiocytic infiltrate; immunohistochemistry showed rare macrophages containing numerous positive amastigotes. The present retrospective study reports, for the first time, a case of a cutaneous lesion by L. infantum occurring in an Italian horse. Pathological and healthy skin samples should be investigated on a larger scale to provide information on the potential clinical impact of EL in the practice, and to define the role of horses in epidemiological ZVL and CanL scenarios.